(untitled) (Bangladesh Journal of Microbiology, 2016)
Prevalence of subclinical mastitis along with the etiological agents and their antimicrobial susceptibility were studied around the city of Dhaka, the capital of Bangladesh. Milk samples from 30 apparently healthy buffaloes were subjected to microbiological examinations while subclinical mastitis was diagnosed based on California Mastitis Test (CTM). Seventy percent of the buffaloes examined were positive for subclinical mastitis. A total of 42 isolates of 5 different species were identified. Among them, Staphylococcus spp. was the most frequently identified bacterial species accounting for 50% of all the isolates, followed by E.coli (28.57%), Enterobacter (14.29%), Bacillus spp. (4.76%) and Proteus spp. (2.38%). Highest resistance was found against amoxicillin (21.43%) where chloramphenicol and ciprofloxac in proved to be a more successful antimicrobial agent, resistance against which wasonly 4.76%. Results from the present study suggest that contagious mastitis controlpractice along with good personal hygiene practice is required for mastitis control in the area. Bangladesh J Microbiol, Volume 30, Number 1-2,June-Dec 2013, pp 1-5